ESTIMATION OF STATURE FROM HANDPRINT ANTHROPOMETRY OF MALAYSIAN CHINESE FOR FORENSIC INVESTIGATION - Moorthy, T. Nataraja; Yin, Tee Yi (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 6 (2016): Indonesian Journal of Legal and Forensic Sciences, 2016)
Stature estimation is an important element in forensic investigation. Literature review shows that handprint anthropometry has provided useful information to estimate stature for identification purposes. Handprints form an important physical evidence frequently available in scenes of crime like burglary, homicide, sexual assault and firearm incidents. The aim of the present study is to derive linear regression equations to estimate stature from hand print anthropometry of Malaysian Chinese. The study sample consists of 100 males and 100 females of Malaysian Chinese, age ranged from 18 to 58 years. Stature and handprints were recorded following standard procedure. Five length measurements and one breadth measurement from each hand with a total of 12 measurements were taken from a subject. The right hand print measurement is larger than the left, showing the bilateral asymmetry but not significant. The result of the study provided population specific linear regression equations to estimate stature from handprints (complete and partial) of Malaysian Chinese.
Keywords: Forensic Science, Forensic anthropology, Stature, handprint, Malaysian Chinese.